Descriptions of two new species of Tarachoptera from Burmese amber (Insecta, Amphiesmenoptera: Tarachoptera) - Mey, Wolfram; Wichard, Wilfried; Müller, Patrick; Wang, Bo (Contributions to Entomology = Beiträge zur Entomologie, 2020)
During examination of new material of Burmese amber three individuals of Tarachoptera were discovered. The inclusions are sufficiently well preserved and allow identification and description of these rare, fossil insects. The species belong to the family Tarachocelidae and are described as Kinitocelis macroptera spec. nov. (†) and Retortocelis spicipalpia spec. nov. (†). The species and their preservations are described in detail, and photos and line drawings are provided for wing venation, head, mouthparts, and abdomen. The hitherto described species of Tarachoptera are summarized in a checklist. Taxonomic acts Kinitocelis macroptera Mey & Wichard, spec. nov. – urn:lsid:zoobank.org:act:E0B1624A-C69E-4B53-851F-4368AC21C614 Retortocelis spicipalpia Mey & Wichard, spec. nov. – urn:lsid:zoobank.org:act:9778E7E2-EEFE-4DC5-B891-54DF114D525C